Civil Liability for the Practice of Closing Brand Labels on Hijab Fashion Products Based on Law Number 20 of 2016 concerning Trademarks - Maspiah, Siti; Anjala, Iffah Nazliya; Wulandari, Niken Ayu; Natania, Nazwa (Rechtsvinding, 2025)
The practice of closing brand labels or cutting labels on hijab fashion products is a form of using brands without rights that is still found in trade activities. This action is carried out by removing or closing the original brand label and recirculating the product without the consent of the registered trademark owner, thus potentially causing losses to the trademark rights holder. This study aims to analyze civil liability for perpetrators of the practice of closing brand labels based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications. The research method used is normative legal research with a legislative approach and a conceptual approach, especially the provisions of Article 83 paragraph (1) of the Trademark Law. The results of the study show that the practice of label cutting is an act that violates the exclusive rights of the brand owner and causes losses both materially and immaterially. Based on the provisions of Article 83 of the Trademark Law, the trademark owner has the right to demand compensation and request the termination of all acts related to the trademark infringement. The conclusion of the study confirms that civil liability has an important role in providing effective legal protection for brand owners as well as maintaining legal certainty and justice in the trade of hijab fashion products.